The Psychological Analysis of Jamie Sullivan’s Behaviors in Nicholas Sparks’ Novel “A Walk to Remember” - Bulan, Nezia Priscila; Ida Setianingsih, Ni Ketut Alit; Winaya, I Made (Humanis, 2019)
The title of this undergraduate thesis is The Psychological Analysis of Jamie Sullivan’s Behaviours in Nicholas Sparks Novel “A Walk to Remember”. The discussion of this study focused on psychoanalysis of the behavior of the main character Jamie Sullivan and the most dominant psychoanalysis concepts of the main character based on Freud's personality theory. Documentation method was applied to collecting the data of this study, which were analysed using descriptive qualitative method; then the result of analysis was presented in the form of sentences using informal method. The result of this study shows that Jamie’s dominant personality in Freud's tripartite personality theory is Superego as she behaves according to the civilized manner. Jamie tends to help others. She makes decisions based on morals and judgments about what is right and what is wrong, and her decisions are based more on moral values.